College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Section P.6 - Factoring - P.6 Exercises - Page 42: 37



Work Step by Step

RECALL: $A^2-2AB+B^2=(A-B)^2$ The given trinomial can be written as: $=(3a)^2-2(3a)(v) + v^2$ The expression above is a perfect square trinomial with $A=3a$ and $B=v$ Factor using the formula above to obtain: $=(3a-v)^2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.